Right ventricular dysfunction in patients with non-severe ischemic mitral regurgitation qualified to cardiosurgery treatment. (4th February 2022) - Piatkowski, R; Budnik, M; Kochanowski, J; Grabowski, M; Opolski, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Right ventricular (RV) dysfunction worsens prognosis in patients (pts) after myocardial infarction (MI). Purpose: The purpose of this study was to assess RV function as a predictor of mortality and hospitalizations due to exacerbation of HF in pts with ischemic mitral regurgitation (IMR) qualified for cardiosurgical treatment - coronary artery by-pass grafting alone (CABGa) or CABG with mitral reconstruction (CABGmr). Methods: We prospectively analyzed 104 pts (M 57, 64 ± 7 years) with non-severe IMR, 3-24 weeks after MI. Effective regurgitation orifice (ERO) was used for quantitative IMR assessment (non-severe ≥10-20 mm²). All the pts were qualified for CABG (multiple vessel coronary disease, ejection fraction (EF)-44 ± 8%). The patients were referred for CABGa (gr.1; n = 77) or CABGmr (gr.2; n = 27) based on clinical assessment, 2D and 3D echo at rest and exercise. Tricuspid annular plane systolic excursion (TAPSE) was acquired to evaluate RV function (measured with M-mode imaging in the 4-chamber view). RV function was related to clinical outcome (median follow-up: 12 months). Results: During the follow-up period of 12 months, 5 deaths (5 %) and 8 hospitalizations (8%) due to exacerbation of HF occurred. With use of the following cut-off points of TAPSE ≤ 12 mm (group I), and TAPSE >12 mm (group 2)—an association was found between the lower TAPSE and increased mortality. In group 1 (n =54 pts), 5 pts (9.2%) died and 6 pts was hospitalized due to HF (11.1%); in group 2 (n =50), no patient died, and 2 pts was hospitalized (4%). There was a significant difference (p = 0.02) in clinical outcomes between group I and II. ROC analysis identified TAPSE ≤12 mm as predictive cut-off for prediction adverse clinical outcome in all study group: (death: sensitivity 80%, specificity 76%, area under curve [AUC] = 0.807 (Fig.1); death and HF hospitalizations: sensitivity 69%, specificity 79%; AUC =0.767). Conclusion: TAPSE is simple and useful quantitative measurement of RV function and have a predictive value in pts with non-severe IMR referred for cardiosurgery treatment.